The use of ICT in teaching by special education teachers in Sichuan, China: determinants and solutions to challenges - She wanBin; Wu Yan (Humanities & Social Sciences Communications, 2025)
Abstract This research examines the factors affecting ICT use in teaching by special education teachers in Sichuan, China. A descriptive survey design was used, with data collected from 550 respondents via a questionnaire. The collected data were analyzed using percentages, means, standard deviations, t tests, and regression analysis. The survey results show that the factors influencing the use of ICT in teaching by special education teachers are multidimensional and complex, with school factors, teacher factors, student factors, and ICT tool factors having a significant impact and showing a linear relationship. Specifically, the lack of ICT personnel, high ICT costs, insufficient ICT resources in school, lack of confidence, lack of experience, and software support in teachers, lack of digital literacy and skills, lack of confidence in using ICT to support learning in students, and lack of suitable teaching ICT tools and complex operation and use collectively affect the status and level of use of ICT in teaching by special education teachers. It is necessary for schools, teachers, students, and other stakeholders to take effective measures to improve.